Differentiation of Human Pluripotent Stem Cells Into Specific Neural Lineages. (4th June 2021) - Chang, Chia-Yu; Ting, Hsiao-Chien; Liu, Ching-Ann; Su, Hong-Lin; Chiou, Tzyy-Wen; Harn, Horng-Jyh; Lin, Shinn-Zong; Ho, Tsung-Jung
Human pluripotent stem cells (hPSCs) are sources of several somatic cell types for human developmental studies, in vitro disease modeling, and cell transplantation therapy. Improving strategies of derivation of high-purity specific neural and glial lineages from hPSCs is critical for application to the study and therapy of the nervous system. Here, we will focus on the principles behind establishment of neuron and glia differentiation methods according to developmental studies. We will also highlight the limitations and challenges associated with the differentiation of several "difficult" neural lineages and delay in neuronal maturation and functional integration. To overcome these challenges, we will introduce strategies and novel technologies aimed at improving the differentiation of various neural lineages to expand the application potential of hPSCs to the study of the nervous system.